2012
DOI: 10.1111/j.1461-0248.2012.01863.x
|View full text |Cite|
|
Sign up to set email alerts
|

Biodiversity effects on ecosystem functioning change along environmental stress gradients

Abstract: Positive relationship between biodiversity and ecosystem functioning has been observed in many studies, but how this relationship is affected by environmental stress is largely unknown. To explore this influence, we measured the biomass of microalgae grown in microcosms along two stress gradients, heat and salinity, and compared our results with 13 published case studies that measured biodiversity-ecosystem functioning relationships under varying environmental conditions. We found that positive effects of biod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
133
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(141 citation statements)
references
References 41 publications
8
133
0
Order By: Relevance
“…These effect sizes are close to those found in a review of 44 species diversity experiments where species mixtures produced on average 72% more biomass than monocultures 31 . It is intriguing that, similarly as in other diversity studies 32 , the benefit of increased epigenetic diversity was greatest under the most realistic environmental conditions where both pathogens and competitors were present. The results of our study are comparable to previous species or within-species diversity experiments not only in terms of effect sizes but also in terms of the shape of the diversity-productivity relationships and the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 80%
“…These effect sizes are close to those found in a review of 44 species diversity experiments where species mixtures produced on average 72% more biomass than monocultures 31 . It is intriguing that, similarly as in other diversity studies 32 , the benefit of increased epigenetic diversity was greatest under the most realistic environmental conditions where both pathogens and competitors were present. The results of our study are comparable to previous species or within-species diversity experiments not only in terms of effect sizes but also in terms of the shape of the diversity-productivity relationships and the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 80%
“…The plant diversity effects on these functions are more pronounced in stress conditions (Steudel et al, 2012) and become stronger with time (Reich et al, 2012). Through resource availability and niche differentiation, increase in plant biomass and species richness favours the accumulation of soil microbial and faunal biomass and abundance that accommodate greater number of species.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of tolerant species was more pronounced at higher levels of species richness than lower one, indicating some type of interactions might be possible between these species. In previous studies also, the selection effect was found to be prevalent under stressful conditions where tolerant species contributed largely to the ecosystem functioning (Boles et al, 2004;Steudel et al, 2012).…”
Section: Role Of Biodiversity Under Abiotic Perturbationmentioning
confidence: 99%
“…On the other hand, the prevalence of antagonistic interactions is the main cause behind negative relationships (Becker et al, 2012;Foster and Bell, 2012). The impacts of abiotic stress on biodiversity-ecosystem functioning relationship of microbial systems are generally found negative (Steudel et al, 2012) or positive in some cases (Li et al, 2010). Bacterial diversity has been found to increase the community stability against both biotic and abiotic environmental perturbations .…”
Section: Introductionmentioning
confidence: 99%